STUDENT PREFERENCE TOWARDS OVO AS A CASHLESS PAYMENT FACILITY (STUDY AT STUDENTS OF FACULTY OF BUSINESS IN SURABAYA CITY) - Padmawidjaja, Liestya; Sutrisno, Timotius F. C. W.; Setiani, Nisa (Universitas Brawijaya, Indonesia, 2020)
This study was used to determine the acceptance preferences of OVO technology in business faculty students in Surabaya using the TAM theory model (Technology Acceptance Model) that focuses on Perceived Efficacy Factors, Perceived Ease of Use, Perceived Usage that is Easy to Use, and Perceptions of Use that are Perceived and Behavior Intentions for Use. OVO service is a mobile application that allows users to transact using electronic money. There is a trend of using electronic money payments using transitions to make transactions easier, more effective, and efficient, but still safe. Survey data were collected from 160 OVO users and analyzed using quantitative methods with multiple linear regression analysis. The results of this study indicate that the Perceived Risks and TAM core constructs such as Perceived Usability and Perceived Ease of Use have been proven to be both partially and simultaneously significant for the Behavior of Intention to Use. This study explains the significant relationship between constructs and discussing this information can be used to increase OVO acceptance among Surabaya students. This research is based on primary data collection and interpretation. This provides comprehensive insights about OVO acceptance to students in the city of Surabaya.